Morphological relationship between the superior cervical ganglion and cervical nerves in Japanese cadaver donors. Issue 2 (29th December 2016) - Mitsuoka, Kazuyuki; Kikutani, Takeshi; Sato, Iwao
Abstract: Introduction: There are various communications between the superior cervical ganglion (SCG) and the vagus and glossopharyngeal nerves. However, little information exists concerning the origin of these sympathetic ganglion branches at the superior, middle, and inferior regions of the human SCG. The aim of this study was to describe the human SCG in a morphometric manner with the communication with cranial and cervical nerves and supply. Methods: This study characterized 72 SCG samples from 54 elderly Japanese human cadavers (30 males, 24 females; 65–100 years old). The SCG size (length, width, and thickness) and location were measured from the jugular foramen. We also defined the communication branches of the SCG to the vagus, glossopharyngeal, cervical, and accessory nerves at three regions (superior, middle, and inferior regions) of the SCG. Finally, we examined the arrangement and origin of the branch communications in detail and confirmed our observations, using histological sections of the SCG. Results: The SCG in all cadaver donors was detected at the C2 and C3 vertebra levels. The number of SCG branches supplied the communicating branches, such as the carotid branch, communicating branch of the vagus nerve, and glossopharyngeal nerve, were frequently detected in the superior region of the SCG (χ 2 = 587.72, df = 26, p < .001). The number of ganglion cells with a large number of neurons per unit area (1 mm 2 ) was most often found in the middle region with shrunken neurons of the SCG compared with other regions. Conclusion: The communication branches of the SCG are mainly connected to the vagus and glossopharyngeal nerves. Characterizing these branches can provide useful data for head and neck ganglion block and surgical treatments. Abstract : Various communications of the superior cervical ganglion (SCG) with the vagus and glossopharyngeal nerves confirmed histological observations of the SCG, using cadavers. The communication site of mainly the cervical nerve, vagus nerve, and glossopharyngeal nerves is an important surgical landmark in head and neck surgery.